Dopamine receptor activation elicits a possible stress-related coping behavior in a wild-caught songbird - Florkowski, Melanie R.; Yorzinski, Jessica L. (PeerJ, 2022)
Animals experience stress throughout their lives and exhibit both physiological and behavioral responses to cope with it. The stress response can become harmful when prolonged and increasing evidence suggests that dopamine plays a critical role in extinguishing the stress response. In particular, activation of the D2 dopamine receptor reduces glucocorticoids and increases coping behavior, i.e., behavioral responses to adverse stimuli that reduce the harmful effects of stress. However, few studies have examined the effects of dopamine on the stress responses of wild species. We therefore tested the hypothesis that activation of the D2 dopamine receptor influences coping-like behavior in a wild-caught species. We recorded behavior of house sparrows (Passer domesticus) before and after they received injections of D2 dopamine agonists, D2 dopamine antagonists, or saline. House sparrows are common in urban environments and understanding how they cope with stress may help us better understand how animals cope with urban stressors. We found that the birds significantly increased biting of inanimate objects after the agonist but there was no change following the antagonist or saline. The biting of inanimate objects may be a mechanism of behavioral coping. This change in biting behavior was not correlated with general movement. This study supports the hypothesis that D2 dopamine receptor activation is involved in the regulation of the stress response in a wild bird.
Keywords: Coping behavior; Dopamine; D2 dopamine receptor; House sparrow; Stress